Perceptions of undergraduate pharmacy students towards online assessments used during the COVID-19 pandemic in a public university in Malaysia. - Abubakar, Usman; Mohd Salehudin, A'isyah Humaira'; Nik Mohd Asri, Nik Afiqah Athirah; Mohammad Rohi, Nur Atiqah; Ramli, Nur Hasyimah; Mohd Khairuddin, Nur Izzah; Saiful Izham, Nur Fariesya; Nasrullah, Siti Hajar; Adam Sa'ad, Auwal (2022)
Abstract Objective: To evaluate the perceptions of undergraduate pharmacy students towards online assessments used during the COVID-19 pandemic. Methods: A descriptive cross-sectional study was conducted using a self-administered, validated and pre-tested online questionnaire. The data were collected from December 2020 to January 2021 and analysed using descriptive and inferential tests. Results: Of the 233 respondents (response rate: 72%), approximately 45% strongly disagree or disagree that online assessment is better than the conventional method of assessment. Only 23.6% were very satisfied or satisfied with online assessment, while 28.8% were very dissatisfied or dissatisfied. About 80% experienced problems with online assessment including failure of portal/online server (63.5%), slow or failure of internet connection (45.5%) and a problem with laptop/gadget (40.8%). Females, final year students, and those who have access to very fast internet speed had significantly better perceptions towards online assessment. Conclusion: Undergraduate pharmacy students have negative perceptions towards online assessment used during the COVID-19 pandemic. Most of the students experienced difficulties with online assessment and this may affect their performances. The challenges identified should be addressed in order to improve the use of online assessment in the future.